Penerapan Metode WASPAS Dengan Pembobotan ROC Dalam Sistem Pendukung Keputusan Pemilihan Ketua Himpunan Mahasiswa Teknik Informatika (HIMATIKA) - Suhaidi Cibro; Putri Ramadhani (Forum Kerjasama Pendidikan Tinggi (FKPT), 2023)
The Head of HIMATIKA is a student who has a leadership position in the HIMATIKA organizational structure and is also one of the students who has been entrusted to lecturers to carry out their duties and develop every activity held by the Budi Darma University campus. Students who serve as chairmen of HIMATIKA must have great responsibility in organizing, directing, and managing every activity on the Budi Darma University Medan campus. So with that the Medan Budi Darma University campus really hopes that in the election of the HIMATIKA chairman it can provide the best results and those who are elected to become the HIMATIKA chairman can be more committed and have great responsibility so that the Budi Darma University campus will be more advanced, quality and become the best campus. The election of the HIMATIKA chairman at Budi Darma University often results in injustice in the mechanism used to elect the HIMATIKA chairman, and there is also a lack of member participation in the election of the HIMATIKA chairman. This will have an impact on the results of the election for the chairman of HIMATIKA and will also affect the development of HIMATIKA. in the election of the chairman of HIMATIKA if the results are not objective or significant, of course it will cause other problems. So with that the process of solving a problem that occurs in the election of a HIMATIKA chairman requires some criteria data including GPA, discipline, vision and mission, organizational experience, and broad insight. From these criteria data, accurate and clear results will be obtained, and the assistance of a system that can solve each of these problems is needed. Where this system is a system that has a very important role in decision making. The system is DSS, where DSS is one of the systems that can assist in solving each problem by requiring data and methods contained in the DSS in order to obtain more relevant information and support in making each decision. In completing this research, the writer has to find the weight value of the criterion data where the writer uses the ROC method to produce the weight value and after that the writer also searches for the ranking value using the WASPAS method. And where to produce ranking values ​​in the WASPAS method, the author must work according to predetermined steps in order to obtain precise and accurate preference values. The ROC and WASPAS methods really help the writer in generating values ​​accurately.